A Study on The Effect of Protein Levels and Balance Lysine / Methioned in Layer Diets With and Without Fish Meal - Budya Satata; Nasroedin (Nasroedin); Soeharto Prawirokusumo (Buletin Peternakan, 1992)
Artikel dalam bentuk PDF